PENGARUH MODEL PEMBELAJARAN KONSTRUKTIVISME TERHADAP KETEPATAN SERVIS BAWAH DALAM PERMAINAN BOLA VOLI SISWA - Subakti, Subakti (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
The problems that exist in SMP Negeri 1 Lenangguar in particular are still low result of lower service precision. Based on the observations of the above measures, it is stated that the results of the lower service precision are still lacking in the learning process and it is necessary to try the constructivism learning model. The purpose of this research is to know the presence or absence of influence of constructivism learning model to the downward service precision in volleyball game of grade 5 students of SMP Negeri 1 Lenangguar academic year 2015/2016 .. The sample of the study amounted to 30 people by using sampling technique systematic. Method of data analysis using statistical analysis by using t-test formula as test of research hypothesis. By searching or comparing the results of pre-test before treatment (Treatment) and final test (post-test) after treatment. The result of hypothesis test using t-test formula obtained 2,194 bigger than t-table 2.045 thus null hypothesis (Ho) rejected and alternative hypothesis (Ha) received. From the results obtained from the results of the study can be concluded that "There is Influence of Constructivism Learning Model Against Low Service Accomplishment in Student Ball Ball Student Class VII SMP Negeri 1 Lenangguar Lessons 2015 - 2016